PERPUSTAKAAN DI ERA GENERASI DIGITAL NATIVE - Sukirwan Arwan (UIN Imam Bonjol Padang, 2020)
Abstract: A library must be able to provide information and provide services in accordance with the needs of the user community (pemustaka). With the development of information technology which is very fast, without realizing it, it has a very big influence on changes in the character and behavior of the community, especially changes in behavior in seeking information. Potential readers in today's digital era are the digital native generation. The digital generation that grew up in the digital era (in an era of very rapid ICT development) has different characters and behaviors from previous generations. The influence of ICT on changes in behavior and character cannot be prevented or avoided as well as a challenge for libraries. Therefore, like it or not, libraries must have the courage to improve themselves to change and improve the quality of their services from various aspects in accordance with the development and changes of the character of the users, if they do not want to be left behind, libraries must be adaptable to change, friendly to the librarian. in order to answer the era of the birth of this net generationKeyword: Digital native generation, library services, librarian competence.Abstrak: Sebuah perpustakaan harus mampu menyediakan informasi serta memberikan pelayanan yang sesuai dengan kebutuhan masyarakat penggunanya (pemustaka). Dengan adanya perkembangan teknologi informasi yang sangat pesat tanpa disadari berpengaruh sangat besar pada perubahan karakter serta prilaku dari masyarakat terutama perubahan prilaku dalam mencari informasi. Pemustaka potensial di era digital saat ini yaitu generasi digital native. Generasi digital yang tumbuh di era digital (di era perkembangan TIK sangat pesat) memiliki karakter serta prilaku yang berbeda dengan generasi-generasi sebelumnya. Pengaruh TIK terhadap perubahan prilaku maupun karakter tersebut tidak bisa dicegah maupun dihindari serta menjadi tantangan tersendiri bagi perpustakaan. Oleh karena itu, mau tidak mau perpustakaan harus berani berbenah diri untuk merubah dan meningkatkan kualitas pelayanannya dari berbagai segi sesuai dengan perkembangan serta perubahan-perubahan dari karakter pemustaka jika tidak ingin ditinggalkan, Perpustakaan harus adaptable with change, friendly dengan pemustakanya Kompetensi pustakawan menjadi kata kunci agar dapat menjawab era lahirnya generasi nett iniKata Kunci: Generasi digital native, layanan perpustakaan, kompetensi pustakawan.